Повість В. Винниченка «Краса і сила» і проза М. Горького: поетика й типологія індивідуальних стилів - Брайко, О. (Слово і Час, 2020)
У статті в компаративному аспекті з'ясовано стильову природу й
функціональну вагу авторських зображально-виражальних засобів. Проаналізовано відмінності в художньому опрацюванні спорідненої тематики на рівні форм і функцій пластичної зображальності, розповідної презентації дії, сюжетно-композиційної цілісності творів. Аналіз доводить
стильову оригінальність українського письменника-початківця. The paper focuses on the functionality and style characteristics of the authors’ expressive means.
It shows differences in the literary handling of similar subjects at the level of forms and functions
of pictorial-like images, narrative presentation of action, the integrity of plot and composition
in the works. The analysis proves the style originality of the Ukrainian aspiring writer.
Gorky’s bright pictorialism with a tendency towards impressionistic images and enthusiastic
evaluation connects his narration to the codes and toposes of a higher, elite culture,
open to aesthetic contemplative perception and intellectual reaction to the action of a work.
While Vynnychenko’s model revises or even rejects external picturesqueness as an attribute
of national realistic style. This feature gets a universal ontological dimension, and the verbal
representation of scenes approaches to the reality of the potential reader’s world.
The internal action in Gorky’s works is characterized by reflection that stays in line with
the literary tradition of the rational interpretation of a character and the logical development
of a plot leading to the disclosure of existential truth. Vynnychenko, using emotionally
perceptible plastic tools of naturalistic psychologism and minimal narrative rhetorical
devices, appeals to universal anthropological experience. The representations of the internal
action by Russian and Ukrainian prose writers reveal the communicative aspects of the
styles. The minimization of the depictive element makes Vynnychenko’s literary model more
adequate to the actual reader’s expectations.